2013
DOI: 10.1175/jas-d-12-0256.1
|View full text |Cite
|
Sign up to set email alerts
|

On Adding Thermodynamic Damping Mechanisms to Refine Two Classical Models of Katabatic Winds

Abstract: The Prandtl and layer-averaged models of katabatic winds contain some nonphysical singularities in the analytical solutions, which give unbounded steady flow anomalies at zero slope angles or adiabatic lapse rates. This study presents some simple refinements of these two classical models, in which the aforementioned singularities are removed when Newtonian cooling and Rayleigh friction are included in the system. It is pointed out that, in the limit of zero slope angles or adiabatic lapse rates, the along-slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…1984, Pielke); however, if Eq. is extended so that it contains additional damping mechanisms, as in Mo (), this zero‐slope singularity is removed. As we are interested here in slopes from, say, a half of a degree and more, the zero‐slope issue is irrelevant here.…”
Section: Weakly Nonlinear Prandtl Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…1984, Pielke); however, if Eq. is extended so that it contains additional damping mechanisms, as in Mo (), this zero‐slope singularity is removed. As we are interested here in slopes from, say, a half of a degree and more, the zero‐slope issue is irrelevant here.…”
Section: Weakly Nonlinear Prandtl Modelmentioning
confidence: 99%
“…van den Broeke, ; Oerlemans and Grisogono, ; Parmhed et al , ; Axelsen and van Dop, ). Further improvements in treating certain shortcomings of the classic Prandtl model are in Mo (). Overall, one of the main drawbacks for most analytic models of katabatic flows, including the classic Prandtl model, is the assumed linearity and prescribed constancy of eddy diffusivity and conductivity (all for the sake of mathematical tractability).…”
Section: Introductionmentioning
confidence: 99%
“…Grisogono () suggested that the assumed constancy of the eddy viscosity in the original Prandtl model produced near‐surface wind gradients that were generally too weak and obtained an unsteady approximate solution of the Prandtl equations for a prescribed slowly varying (in slope‐normal coordinate) eddy viscosity. Mo () extended the McNider () study of oscillations in katabatic flows by including a Newtonian cooling term in the layer‐averaged thermal energy equation.…”
Section: Introductionmentioning
confidence: 99%